Analysis of the Function of Religious Courts in Resolving Family Conflicts in Indonesia - Haris Fhadillah Butar Butar; Madan Syairazi Zega (PT ARFA DIGITAL TECHNOLOGY, 2025)
The Religious Court as a court of first instance is a court that acts to receive, examine and decide every application or lawsuit at the earliest and lowest stage. The Religious Court serves as a primary court, receiving and adjudicating cases submitted by the public at the initial stage of legal proceedings. The researcher aims to examine this discussion to find out how religious justice works in resolving conflicts in Indonesia and what the function of religious justice itself is. Qualitative research methods with an analytical descriptive approach allow researchers to gain an in-depth understanding of the phenomenon being studied. By using sources such as books, journals and articles, this research can gain rich insight into relevant theories and then analyze them carefully. From this research it can be concluded that religious justice has the function of upholding the true truth of what is expressed and demanded by the parties without exceeding or reducing it, especially in relation to civil cases, whereas in criminal cases the search for the real truth is absolutely not limited to what the defendant has done. ,